(untitled) (International Journal of Education in Mathematics, Science and Technology, 2014)
Digital content is increasingly present in U.S. K-12 classrooms, with a current push by federal officials to increase the rate at which digital textbooks are adopted. While some teachersâ use of electronic resources involves locating activities and lessons from various internet sites, textbook and educational software companies have begun to develop comprehensive programs that can supplement if not fully replace traditional paper textbooks. Digital platforms can be transformative, with possibilities for frequent updating, access to multimedia resources, connection to virtual communities, lower production and distribution costs, and customized instruction. However, there have been no attempts to analyze specific programs in mathematics education with respect to these and other features, a gap we seek to address. In this article, we developed and applied a framework to analyze a representative sample of digital curriculum programs in order to help educators better understand characteristics of these materials. We documented two distinct curriculum types, individualized learning programs and digitized versions of traditional textbooks. While the programs offered some of the features identified as transformative, particularly with respect to assessment systems that rapidly and visually report student performance, there were many features that did not take full advantage of the digital medium.